Analisis Variasi Sapaan Dalam Buku Teks Bahasa Indonesia Kelas X Edisi Revisi: Kajian Sosiolinguistik - Erlin Atifah Azzahrah; Balqis Aisyah Arifah; Mia Kusumawati; Elen Inderasari (Jurnal Ilmiah Dikdaya, 2026)
This research explores the variation of greetings in Indonesian Textbook Class X Revised Edition by using Sociolinguistic approach. The purpose of this study is to describe the forms of greetings and identify the factors that influence their use in the learning context. This research uses descriptive qualitative method with data collection techniques in the form of reading and recording, and analyzed using Spradley's model. The findings of this study show that there are six forms of greeting variations, namely proper names, persona pronomina, kinship, title, rank or position, and profession. In addition, the selection of greetings is influenced by situational factors, age, social status, familiarity, and kinship. This finding confirms that the variety of greetings in textbooks reflects the social and cultural dynamics of society, and has an important role in supporting effective, contextual, and polite Indonesian language learning. This research contributes to the development of teaching materials towards social context and communication.